Pengelolaan Sampah Dalam Mendukung Pengembangan Pariwisata Berkelanjutan Di Kabupaten Gianyar - Putra, I Wayan Sujana; Dewi, Nyoman Diah Utari; Widanti, Ni Putu Tirka (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Gianyar Regency is one of the tourist destinations in Bali. This tourist area is certainly not free from various problems, both problems that can be easily overcome and problems that can hinder the development of tourism itself. Common problems are related to waste management. Based on these conditions, the purpose of this study is to determine waste management in supporting the development of sustainable tourism in Gianyar Regency. The research methodology used in this study is qualitative research with observation. The data sources used are secondary data sources. Secondary data in this study are data obtained from documentation or literature studies from the research locus. The results of the study indicate that waste management that has been carried out in Gianyar Regency is sorting waste from households and scheduling waste delivery according to its source to the final disposal site. Waste sorting activities starting from households have a significant impact on environmental cleanliness and the development of sustainable tourism in Gianyar Regency.